Efektivitas Pengelolaan Sampah (Studi Kasus Upt Pengelolaan Sampah Bangkonol Kabupaten Pandeglang) - Sumarna, Gian (NIAGARA Scientific Journal, 2024)
Waste management services are included in public services which aim to serve the community in managing the waste produced. In waste management services, good performance is needed so that waste management can run effectively. In general, the definition of effectiveness is a level of success produced by a person and organization in a certain way in accordance with the goals to be achieved. According to the Big Indonesian Dictionary (KBBI), effectiveness is the usefulness of activeness and the existence of compatibility in an activity between a person carrying out a task and the goals to be achieved. In other words, the more plans are successfully achieved, the more an activity is considered effective. Waste management at the Bangkonol Waste Management UPT, Pandeglang Regency has not been effective. This can be viewed from several aspects, namely, achieving the objectives of the Bangkonol Waste Management UPT, whose objectives have not yet been fully achieved. Judging from the aspect of duties or functions, the Bangkonol Waste Management UPT is apparently still lacking in carrying out its duties and functions. Aspects of plans or programs related to planning or determining programs to be achieved by the Bangkonol Waste Management UPT from several programs have not yet been implemented as planned, because they are hampered by obstacles which have resulted in several programs not being implemented to date. In terms of the provisions and regulations, it is in accordance with the rules and regulations, but in terms of management it is still not in accordance with the regulations